Vocational High School Students’ Difficulties in Practicing Speaking - Farida Aryani; Farid Noor Romadlon; Agung Dwi Nurcahyo (Prominent, 2025)
English is becoming essential in this quickly changing world because it is crucial for practically every aspect of life, especially communication. Speaking skills is a foundation for being able to communicate in English. However, many students still find it challenging to practice speaking English because it is not the mother tongue in Indonesia. This study investigated students' difficulties and the factors that cause them in English speaking practice. 80 students of Grade 10 Accounting students at SMK PGRI 2 Kudus were the participants in this study. A qualitative method was applied and the data of this study were collected through questionnaires and in-depth interviews. The questionnaire results revealed that students have difficulties in English practice; inhibition, nothing to say, low participation, and mother tongue use with "nothing to say" as the dominant difficulty. The factors that cause these difficulties include clustering (difficulty arranging sentences), redundancy (not knowing to explain correctly), still unfamiliar with the reduced form, low speaking performance, lack of vocab and not understanding what others are saying, low rate of delivery, and difficulty in pronunciation, stress, and intonation with clustering as the dominant factor. Regarding the dominant difficulty and its factor in the result of this study, the researcher suggests that teachers should always introduce new vocabulary daily so that students' vocabulary continues to increase. Moreover, the teacher should give the students an easy way to construct good sentences in speaking because they are still confused about arranging a correct sentence when practicing speaking.